2015
DOI: 10.1128/iai.02897-14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Protection against Clostridium difficile Infection by the Monoclonal Antitoxin Antibodies Actoxumab and Bezlotoxumab

Abstract: dClostridium difficile infection (CDI) represents the most prevalent cause of antibiotic-associated gastrointestinal infections in health care facilities in the developed world. Disease symptoms are caused by the two homologous exotoxins, TcdA and TcdB. Standard therapy for CDI involves administration of antibiotics that are associated with a high rate of disease recurrence, highlighting the need for novel treatment paradigms that target the toxins rather than the organism itself. A combination of human monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 47 publications
0
65
0
1
Order By: Relevance
“…To better understand how in vitro potency can predict in vivo clinical efficacy, it is relevant to correlate in vitro neutralization of specific strains with in vivo clinical efficacy against these same strains. In this regard, actoxumab-bezlotoxumab was efficacious against ribotype 027 strains in a gnotobiotic piglet infection model (22) and in mouse models of primary and recurrent CDIs (23). Furthermore, the antibodies reduced the rate of recurrent CDIs in patients infected with ribotype 027 strains to the same extent as in the overall patient population (although the reduction did not reach statistical significance; P ϭ 0.06) (7).…”
Section: Discussionmentioning
confidence: 87%
“…To better understand how in vitro potency can predict in vivo clinical efficacy, it is relevant to correlate in vitro neutralization of specific strains with in vivo clinical efficacy against these same strains. In this regard, actoxumab-bezlotoxumab was efficacious against ribotype 027 strains in a gnotobiotic piglet infection model (22) and in mouse models of primary and recurrent CDIs (23). Furthermore, the antibodies reduced the rate of recurrent CDIs in patients infected with ribotype 027 strains to the same extent as in the overall patient population (although the reduction did not reach statistical significance; P ϭ 0.06) (7).…”
Section: Discussionmentioning
confidence: 87%
“…Bezlotoxumab was confirmed to bind to epitopes in the carbohydrate-binding domain of TcdB, possibly explaining its efficacy [40]. In mouse models, bezlotoxumab mutated in the Fcγ receptor binding site was as protective as unmodified Ab, suggesting that direct toxin neutralization is likely the mechanism of protection in CDI [41]. In contrast, the failure of actoxumab in human trials provides additional evidence that TcdB is more damaging in human disease, and also may explain the discrepancies in earlier studies that found conflicting reports of whether naturally occurring anti-TcdA antibodies protect against CDI.…”
Section: Immunotherapy For CDImentioning
confidence: 97%
“…C. difficile infection can complicate the use of broad-spectrum antibiotics, causing a severe infectious toxigenic colitis rising in incidence and incurring significant morbidity and mortality [101]. Human monoclonal antibodies that neutralize C. difficile toxins A and B, lower TNFa levels and improve survival in preclinical mouse models are currently under investigation [102][103][104]. A phase II study compared treatment with monoclonal antibodies against toxins A and B combined with standard antibiotic treatment to antibiotic treatment alone.…”
Section: Difficile Colitismentioning
confidence: 99%